The Effect Of Risk Factors And Clinical Symptoms On Comorbid And Non-Comorbid Disease In Covid-19 Patients At Royal Prima General Hospital Medan - Putri Gly De La Glory Ginting; Marlinang Isabela Silalahi; Sri Lestari Nasution (CV. Inara, 2022)
Covid-19 is a disease caused by infection with SARS-CoV-2 and causes a variety of clinical symptoms ranging from asymptomatic to critical symptoms, depending on various risk factors. The purpose of this research is to analyze the effect of risk factors (age, gender, occupation) and clinical symptoms (asymptomatic, mild, moderate, severe, critical) on comorbid and non-comorbid diseases in Covid-19 patients at General Hospital Royal Prima Medan. This Paper research used is quantitative research with secondary data collection in April-June 2021. The number of research samples was 308 comorbid patients and 308 non-comorbid patients. Data were analyzed univariately to see a descriptive picture, bivariate using chi-square test, and multivariate using binary logistic regression test. The results of this study are: based on age risk factors, the highest age group is 46-65 years (40.1%). The conclusions in this study are there is an influence of risk factors for age, gender, and mild, moderate, and severe clinical symptoms on comorbid and non-comorbid diseases in Covid-19 patients at Royal Prima Hospital Medan.